Strengthening start-up ecosystems for bio-based innovations in the food sector: Lessons from East Africa - Paul Nyangau; Zewdu Abro; Julius Ecuru; Menale Kassie; Shira Mukiibi; Heike Baumüller; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2024)
The bioeconomy is emerging as a significant driver of economic growth and sustainability thinking globally and in East Africa. Leveraging bioscience knowledge, tools and techniques, research organisations and start-ups are developing improved bio-based products including crop varieties, as they respond to the region's commitment to sustainability transition. This study evaluated the biobased start-up ecosystem in four countries in East Africa. The study used a qualitative approach which included document review, key informant interviews (KIIs) with startup managers and focus group discussion (FGD) with stakeholders in the start-up ecosystem in East Africa. In the whole region, probably less than 30 successful start-ups relating to the emerging bioeconomy were established within the last five years. The findings show that access to finance remains a critical challenge for biobased start-ups in East Africa. While there is growing interest from both public and private investors, many start-ups struggle to secure funding due to factors such as stringent collateral requirements and high-interest rates especially for young innovators. Additionally, allocated funds for research initiatives aimed at developing bio-based products, processes and technologies appear to be insufficient to meet the growing financial capital needs of the startups in the food sector. Findings also show that start-ups operate below capacity because of shortage of raw materials due to weak supply chains and to a great extent weak links to markets. It was found that lack of specialization among start up ecosystem players hinders the support provided to entrepreneurs. The study recommends increased collaboration between national research institutions, universities and international partners in the creation of knowledge, and translating the knowledge to innovation in the region. Additionally, leveraging sector-specific expertise and providing incentives for start-ups and innovation hubs are necessary for building a more resilient and inclusive innovation ecosystem for the food system in East Africa.
Keywords: G3; M13; O14; Q57; 330; Bioeconomy; East Africa; Food; Innovation Ecosystem; Start-ups